Construction and analysis of the execution model for Chinese primary school teachers’ extracurricular physical education service teaching: a case study of Henan Province - Ma, Tingyu; Wang, Jieni; Zhang, Kejia; Cao, Leichang (Frontiers in Psychology, 2025)
The execution ability of teachers is the key to promoting the deepening of educational reform and adapting to educational development. By studying the execution ability of teachers in after-school services, scientific bases can be provided for formulating relevant policies and proposing improvement strategies, thereby providing positive contributions to the development of education. The construction of a structural model and visualization of the structure of after-school service execution can directly promote the professional development of teachers and advance the progress of education. This study used the literature review, interview, questionnaire survey, and data analysis methods to preliminarily develop a teachers’ after-school sports service teaching execution force table, and explored the structural model of teachers’ after-school sports service teaching execution force. Exploration factor analysis results show that the structure model of sports service teaching execution force consists of nine first-order factors: the abilities to (1) understand after-school sports service policies, (2) understand after-school sports service curriculum standards, (3) understand the expectations of stakeholders in after-school sports services, (4) develop after-school sports service resources, (5) design after-school sports service teaching, (6) implement after-school sports service processes, (7) evaluate the learning effects of after-school sports service students, (8) evaluate after-school sports service curriculum, and (9) of teachers to reflect on after-school sports services. Further verification indicated that the second-order dimension consists of the abilities to understand, operate, and evaluate after-school sports services. Lastly, confirmatory factor data show that the nine-factor structural models have the best fit.